Long-term prospects for viable diversified agriculture with increased contribution to export earnings - Chase, V. (OECS St John'sAG, 1987)
Reviews the current agricultural situation in the OECS territories. Outlines reasons justifying agricultural diversification in specific areas of research viz. crop and animal production programs and integrated production systems programs. Identifies substitute crops for diversification and outlines main diversification projects being implemented in the OECS.